PROSES KREATIF MENULIS USAHA INTERPRETASI NILAI PENDIDIKAN DALAM KARYA SASTRA - Sutardi Sutardi; Ernaningsih Ernaningsih (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The idea in this paper is an effort to optimize learning to appreciate literary works during the Pandemic. This paper will map the problems of literary learning during the Covid-19 pandemic by looking at the creative process of writing as an effort to interpret the value of education in literary works. The problem of learning literary appreciation carried out by teachers and students during this Pandemic will be revealed some of the creative processes of writing and its steps. By writing literary works, the hope for increasing the understanding and interpretation of literary works can be maximized and the purpose of appreciation in shaping educational values can be achieved.